Characterization of an energy dispersive X-ray fluorescence imaging system based on a Micropattern Gaseous Detector - Silva, A. L. M. (2011)
An Energy Dispersive X-ray Fluorescence (EDXRF) imaging system based on a Micropattern Gas Detector has already shown good results for di erent applications. An X-ray tube, a pinhole camera and a Micro-Hole and Strip Plate (MHSP) based detector are the main components of the experimental system. The detector uses an MHSP in a Xe atmosphere at 1 bar, acting as a photon counting device, i.e., it is capable to record each single event retaining the energy and the interaction position (2D-sensitive detector) information of the incident photon, demonstrating to be a promising device for EDXRF imaging applications. This work presents studies of energy resolution, energy linearity and spatial resolution/elemental mapping as a function of image magni cation of the system.